ANALISIS RASIO KEUANGAN PERBANKAN SEBAGAI ALAT UKUR KINERJA KEUANGAN BANK (Studi Kasus PT. Bukopin (Persero), Tbk periode 2014-2015) - Bogy Febriatmoko; Sartika Wulandari; Widhian Hardiyanti (Dinamika Akuntansi Keuangan dan Perbankan, 2016)
This study aims to describe the financial performance of banks based on the results of banking financial ratio analysis. The type of research used in this study is descriptive research type using a quantitative approach. The results of banking financial ratio analysis on liquidity ratio analysis shows the condition of financial performance of PT. Bukopin (Persero), Tbk period 2014-2015 can be said good. The average CR of 17.57%, RR 539,239 LDR of 85.12%, LAR of 68.97% has met the standards set by Bank Indonesia and has also exceeded the average of the Commercial Bank of the Company (BUP). The results of solvency ratio analysis, financial performance condition of PT Bukopin (Persero) Tbk in 2014-2015 can be said good because the average CAR of 13.88%, LDAR of 2.39%, DER of 1057.92%, the value has been meet the requirements of Bank Indonesia. In the analysis of earnings ratio, the condition of financial performance can be said not good, because the average on ROA is only 0.97%, ROE of 11.20%, and BO / PO of 88.39%, NPM of 9.49%, the value is still below the average BUP and under the terms of Bank Indonesia. From all financial ratio analysis hence can be known how financial condition of PT. Bukopin (Persero), Tbk. Keywords: financial ratios, corporate financial condition